COMPARISON BETWEEN THE RESULTS OF THE PILE BEARING CAPACITY ANALYSIS BASED ON EMPIRICAL METHOD AND FINITE ELEMENT METHOD USING THE RESULTS OF DYNAMIC ANALYSIS ON THE FIELD - Michael Antonie Prayogo; Herman Wahyudi; Indrasurya B Mochtar (Institut Teknologi Sepuluh Nopember, 2021)
There are many methods for calculating the bearing capacity of a pile foundation. The problem is finding the most representative method for analysis dynamic load testing (PDA) results in the field. This study only covers the areas of West Surabaya and North Surabaya. The method used to analyse the bearing capacity of the pile foundation in this study is the empirical method, namely the Schmertmann, Meyerhof, and L. Decourt method and the finite element method (FEM.). This research only for calculating the bearing capacity of precast pile foundations. The initial stage of the research was to collect soil survey data in the form of N-SPT boring logs and PDA test results in the area. Then the calculation analysis is carried out using the empirical method and FEM, which will be compared with the PDA results. FEM analysis uses dynamic load with pile-driving modelling, which is similar to PDA testing. After comparison, the researchers find some ratios for each calculation method and results of PDAs in the field of study. This study indicates that the most representative method for PDA results in West Surabaya is the Meyerhof method. For the North Surabaya area, these methods have not shown expected results of PDA results in the field